2016
DOI: 10.1080/19336950.2015.1124311
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction of β2e with phosphoinositides: A comparative study between β2e and MARCKS

Abstract: Voltage-gated calcium (Ca V ) channels are responsible for Ca 2C influx in excitable cells. As one of the auxiliary subunits, the Ca V b subunit plays a pivotal role in the membrane expression and receptor modulation of Ca V channels. In particular, the subcellular localization of the b subunit is critical for determining the biophysical properties of Ca V channels. Recently, we showed that the b2e isotype is tethered to the plasma membrane. Such a feature of b2e is due to the reversible electrostatic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…6, B and C ). It is known that basic amino acids and aromatic residues are major determinants of the membrane incorporation of peripheral proteins ( Gelb et al, 1999 ; Miranda-Laferte et al, 2014 ; Kim et al, 2015a , b ; Kim and Suh, 2016 ). Thus, we investigated whether mutant forms of B domain peptide (B Ala and Phe Ala ) can interact with liposomes containing anionic lipids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6, B and C ). It is known that basic amino acids and aromatic residues are major determinants of the membrane incorporation of peripheral proteins ( Gelb et al, 1999 ; Miranda-Laferte et al, 2014 ; Kim et al, 2015a , b ; Kim and Suh, 2016 ). Thus, we investigated whether mutant forms of B domain peptide (B Ala and Phe Ala ) can interact with liposomes containing anionic lipids.…”
Section: Resultsmentioning
confidence: 99%
“…9 ). It has been reported that both basic and aromatic residues of the N terminus play essential roles in the electrostatic interaction of the Ca V β2e subunit with the plasma membrane ( Miranda-Laferte et al, 2014 ; Kim et al, 2015a , b ; Kim and Suh, 2016 ). Here, we also found that the interaction of the HOOK region with the plasma membrane depends on both polybasic and hydrophobic residues within the B domain.…”
Section: Discussionmentioning
confidence: 99%
“…There are some examples in which aromatic amino acids help proteins insert themselves into membranes. Studies of the membrane-tethered β2 subunit of voltage-gated Ca 2+ channel (Ca V ) suggested that Ca V binds to the plasma membrane through electrostatic and hydrophobic interactions with basic and aromatic residues (Miranda-Laferte et al, 2014; Kim et al, 2015; Kim and Suh, 2016; Park et al, 2017). In a study of phospholipase A 2 (PLA 2 ), tryptophan plays an important role in binding to the plasma membrane, and removal of tryptophan at the interface lowers the affinity of PLA 2 to the membrane (Gelb et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies using Dr-VSP as a molecular tool for acute depletion of PtdIns(4,5)P 2 (85,(87)(88)(89) showed that binding of the ␤-subunit to the cell membrane is a critical determinant for both voltage-dependent inactivation and PtdIns(4,5)P 2 sensitivity and that a NH 2 -terminal region of the ␤-subunit, called the HOOK region, which contains clusters of multiple charged residues, is critical for the membrane interaction of ␤-subunits (139). All these studies were done with heterologously expressed Ca V in mammalian cells.…”
Section: K ϩ Channelsmentioning
confidence: 99%